Sex Disparities in Outcomes Following Major Liver Surgery: New Powers of Estrogen?. Issue 5 (27th November 2022) - Birrer, Dominique L.; Linecker, Michael; López-López, Víctor; Brusadin, Roberto; Navarro-Barrios, Álvaro; Reese, Tim; Arbabzadah, Sahar; Balci, Deniz; Malago, Massimo; Machado, Marcel A.; Ardiles, Victoria; Soubrane, Olivier; et al.
Abstract : Aim: To explore potential sex differences in outcomes and regenerative parameters post major hepatectomies. Background: Although controversial, sex differences in liver regeneration have been reported for animals. Whether sex disparity exists in human liver regeneration is unknown. Methods: Data from consecutive hepatectomy patients (55 females, 67 males) and from the international ALPPS (Associating-Liver-Partition-and-Portal-vein-ligation-for-Staged-hepatectomy, a two stage hepatectomy) registry (449 females, 729 males) were analyzed. Endpoints were severe morbidity (≥3b Clavien-Dindo grades), Model for End-stage Liver Disease (MELD) scores, and ALPPS interstage intervals. For validation and mechanistic insight, female-male ALPSS mouse models were established. t, χ 2, or Mann-Whitney tests were used for comparisons. Univariate/multivariate analyses were performed with sensitivity inclusion. Results: Following major hepatectomy (Hx), males had more severe complications ( P =0.03) and higher liver dysfunction (MELD) P =0.0001) than females. Multivariate analysis established male sex as a predictor of complications after ALPPS stage 1 (odds ratio=1.78; 95% confidence interval: 1.126–2.89; P =0.01), and of enhanced liver dysfunction after stage 2 (odds ratio=1.93; 95% confidence interval: 1.01–3.69; P =0.045). Female patients displayed shorter interstage intervals (<2 weeks, 64% females versus 56% males, P =0.01), however, not in postmenopausal subgroups. In mice, females regenerated faster than males after ALPPS stage 1, an effect that was lost upon estrogen antagonism. Conclusions: Poorer outcomes after major surgery in males and shorter ALPPS interstage intervals in females not necessarily suggest a superior regenerative capacity of female liver. The loss of interstage advantages in postmenopausal women and the mouse experiments point to estrogen as the driver behind these sex disparities. Estrogen's benefits call for an assessment in postmenopausal women, and perhaps men, undergoing major liver surgery.